Unleashing innovation and entrepreneurship in Europe: people, places and policies - Leceta, Jose Manuel; Renda, Andrea; Könnölä, Totti; Simonelli, Felice (Brussels, 2017)
"This report sets out the elements for the design of a streamlined and future-proof policy on innovation and entrepreneurship in Europe. It is the result of a collective effort led by CEPS, which formed a Task Force on Innovation and Entrepreneurship in the EU, composed of authoritative scholars, industry experts, entrepreneurs, practitioners and representatives of EU and international institutions. The result of these deliberations is a set of policy recommendations aimed at improving the overall environment and approach for entrepreneurship and innovation in Europe and a new paradigmatic understanding of the role that innovation and entrepreneurship can and should play within the overall context of EU policy. These recommendations are based on a new, multi-dimensional approach to both innovation and entrepreneurship as social phenomena and to the policies that are meant to promote them."